Remote Sensing of the Terrestrial Hydrologic Cycle - Tang, Qiuhong; Qi, Youcun; Wang, Zhihui; Pan, Yun (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book provides a practical introduction to remote sensing applications for detecting changes in the terrestrial water cycle and understanding the causes and consequences of these changes. Covering a wide range of innovative remote sensing approaches for hydrological study, this book contributes significantly to the knowledge base of hydrology in the Anthropocene, i.e., global change hydrology. It is an excellent reference for students and professionals in the fields of hydrology, climate change, and geography.